Using a Gratitude Intervention to Improve the Lives of Women With Breast Cancer: A Daily Diary Study - Sztachańska, Joanna; Krejtz, Izabela; Nezlek, John B. (Frontiers in Psychology, 2019)
Gratitude can be understood in two ways: as a short state of being grateful for things and people, and as a disposition, which allows people to notice and appreciate positive aspects of life. Research suggests that focusing on reasons for being grateful promotes various aspects of well-being. The present study examined the effectiveness of a gratitude intervention for women with breast cancer. Each day for two weeks, 42 women with breast cancer described their psychological well-being, social support, and coping strategies. Women in the intervention condition reported the reasons why they felt grateful that day. Moreover, all participants took part in a pre-test session where trait measures were taken to control for dispositional differences. Listing the reasons for gratitude triggered higher levels of daily psychological functioning, perceived more support, and used adaptive coping strategies more often. These results suggest that gratitude interventions may improve the lives of oncological patients.